An optional European contract law code: advantages and disadvantages - Wolfgang Kerber; Stefan Grundmann (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2006)
Should the EU introduce an Optional European Contract Law Code and what should it look like? By applying economic theories of federalism and regulatory competition (legal federalism), it is shown why an Optional Code would be a very suitable legal instrument within a two-level European System of Contract Laws. By allowing private parties choice of law to a certain extent, it can combine the most important advantages of centralisation and decentralisation of competences for legal rules. Through differentiated analyses of three kinds of contract law rules (mandatory substantive rules, mandatory information rules and facilitative law), important conclusions can be reached: which kinds of contract law rules are most suitable to be applied on an optional basis (e.g. facilitative law) and which might be less so (e.g. information regulations). Furthermore a number of additional general conclusions about the design and scope of an Optional EU Code and some conclusions in regard to sales law are derived.
Keywords: H7; K12; K33; 330; contract law; European Union; legal federalism; regulatory competition; EU-Recht; Föderalismus; Institutioneller Wettbewerb; Rechtsökonomik; Theorie